Indicators of life success from the perspective of individuals with traumatic brain injury: a scoping review. Issue 2 (16th January 2023) - Nalder, Emily; King, Gillian; Hunt, Anne W.; Hartman, Laura R.; Szigeti, Zara; Drake, Emma; Shah, Riya; Shahzad, Maryam; Resnick, Myles; Pereira, Giles; Lenton, Erica
Abstract: Purpose: The purpose was to synthesize qualitative literature and identify indicators of life success (positive life outcomes and experiences) that can help in understanding resiliency in the context of traumatic brain injury (TBI). Methods: This scoping review involved searching nine online databases for population (TBI) and context (qualitative literature). Searches retrieved 42 852 articles and, after two-stage screening, 76 articles met the inclusion criteria of reporting indicators of life success from the perspective of individuals with TBI. Results: Most studies were conducted in North America, Australia, or Europe. Participants were people living with TBI (mild to severe), of all age ranges. Positive life experiences were organized within four domains: understanding of oneself and one's life, social relationships and interaction, doing (engagement in activities, sense of control and accomplishment), and hope for the future. Conclusions: The positive life experiences reflect both processes and outcomes (indicators of success) and highlight the need for a multidimensional approach when seeking to understand resiliency following TBI. The transactional framework of life experiences can be applied in future TBI resiliency research to understand how individuals negotiate adversity through experiences promoting understanding of oneself and the world, social relationships, engagement in activity and hope. Implications for rehabilitation: Rehabilitation services should consider how to afford opportunities for engagement in activity, social interaction, meaning making (i.e., coming to new understandings), and hope. With respect to engaging in activity and social relationships, having social interaction, being understood, being active and productive, having autonomy, and having accomplishments, reflect important experiences to enable within rehabilitation services. Rehabilitation professionals should consider how providing opportunities for their clients to have positive life experiences may contribute toward an adaptive and empowered mindset.